2016
DOI: 10.1007/s40415-016-0331-6
|View full text |Cite
|
Sign up to set email alerts
|

Allomorphic growth of Epipremnum aureum (Araceae) as characterized by changes in leaf morphophysiology during the transition from ground to canopy

Abstract: The aroid vine Epipremnum aureum (L.) Engler has an allomorphic growth throughout its ascent into the forest. In the literature, the allomorphic increase in leaf area of aroid vines was hypothesized to improve its light foraging capacity. This study aims to test this hypothesis by characterizing nitrogen allocation, chlorophyll fluorescence, and morphophysiological and anatomical changes at leaf level along a vertical ascension of E. aureum toward the canopy. Leaf samples were chosen to represent the transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Ray (1990Ray ( , 1992 characterized the allomorphy of aroid vines at the leaf and shoot levels. There are no morphophysiological data (French, 1987) in the literature comparing terrestrial and aerial roots of aroid vines to evaluate whether modifications during habitat transition are observed, as they have been in the stem and leaves (Filartiga et al, 2014;Mantovani et al, 2017). In this work, we demonstrate that changes in root morphophysiology are correlated with habitat transition in the aroid vine R. oblongata from soil to canopy.…”
Section: Introductionmentioning
confidence: 62%
“…Ray (1990Ray ( , 1992 characterized the allomorphy of aroid vines at the leaf and shoot levels. There are no morphophysiological data (French, 1987) in the literature comparing terrestrial and aerial roots of aroid vines to evaluate whether modifications during habitat transition are observed, as they have been in the stem and leaves (Filartiga et al, 2014;Mantovani et al, 2017). In this work, we demonstrate that changes in root morphophysiology are correlated with habitat transition in the aroid vine R. oblongata from soil to canopy.…”
Section: Introductionmentioning
confidence: 62%
“…The absorption of water and nutrients that slide through the host's trunk would represent a complementary way of obtaining resources (Benzing, 1990) for aroid vines rooted in the forest floor (Zotz, 2013). For R. oblongata, it is important to note that both root types feature trichomes that directly adhere to the host (Mantovani et al, 2017), that anchor roots are more frequent per individual plant than feeder roots (e.g., mean of 94 anchor against 10 feeder roots per individual from size class VI) (Filartiga et al, 2014), and that the horizontal water transport of anchor roots is not constrained by gravity as it is in vertical feeder roots (McCulloh and Sperry, 2005). However, the capacity of anchor roots of aroid vines to absorb and transport water has never been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Allometric modifications in the shape and hydraulic architecture of the vegetative body can optimize light, carbon and water flux in plants, minimizing constraints imposed by vertical growth. For aroid vines, the few studies done with light foraging indicate that large leaves at canopies have higher photosynthetic capacity (measured via chlorophyll fluorescence) than leaves positioned near the soil (Filartiga et al, 2014;Mantovani et al, 2017), and it is known that this is dependent on correspondingly high water flux (McCulloh and Sperry, 2005). While allomorphic changes are commonly reported for shoots and leaves of aroid vines (López-Portillo et al, 1990;Mantovani et al, 2017), the results herein reported show that functional allomorphy could also be extended to the aerial roots, both anchor roots, when they exist, and feeder roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A) were found in flowering state on a single branch of Mangifera indica from the plant collection of the Rio de Janeiro Botanical Garden. The climate in the study area is detailed in Mantovani et al (2017). Although few individuals present "grouped rosettes" ( Pridgeon et al 2003), which are represented by two or three interconnected ramets with one inflorescence each, thirty-five flowering individuals of L. ceracifolia represented by only one ramet with one mature inflorescence were collected for the study (Fig.…”
Section: Methodsmentioning
confidence: 99%